1986
DOI: 10.1029/jd091id11p11803
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission during a cultivation period from an Italian rice paddy

Abstract: CH4 release rates from rice paddies were measured in Vercelli, Italy, in 1983 during a complete vegetation period, using a static box system. The rice paddies were found to be a source of atmospheric methane during the time of flooding. The CH4 release rates range between a few milligrams of CH4 per square meter per hour and 51 mg CH4 m−2 h−1 and show a seasonal variation with maximum emission rates between tillering and flowering. Averaged over the complete vegetation period, the CH4 release rate accounts for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(117 citation statements)
references
References 21 publications
8
107
1
1
Order By: Relevance
“…Our estimate is in the middle of current estimates of 26-120 Tg CH 4 yr −1 (Fig. 13c) (Olivier et al, 2005;Cao et al, 1995;Yan et al, 2009;Chen and Prinn, 2006;Wuebbles and Hayhoe, 2002;Cao et al, 1998;Holzapfelpschorn and Seiler, 1986;Seiler et al, 1984;Scheehle et al, 2002;Sass, 1994). For instance, Cao et al (1998) estimated global emissions from rice paddies to be ∼53 Tg CH 4 yr −1 using MF rice paddy areas.…”
Section: Global Simulation Of Rice Paddiessupporting
confidence: 49%
“…Our estimate is in the middle of current estimates of 26-120 Tg CH 4 yr −1 (Fig. 13c) (Olivier et al, 2005;Cao et al, 1995;Yan et al, 2009;Chen and Prinn, 2006;Wuebbles and Hayhoe, 2002;Cao et al, 1998;Holzapfelpschorn and Seiler, 1986;Seiler et al, 1984;Scheehle et al, 2002;Sass, 1994). For instance, Cao et al (1998) estimated global emissions from rice paddies to be ∼53 Tg CH 4 yr −1 using MF rice paddy areas.…”
Section: Global Simulation Of Rice Paddiessupporting
confidence: 49%
“…Temperature sometimes has an important effect on C b flux in various ecosystems (Holzapfel-Pschorn and Seiler 1986, Wang 2001, Edwards et al 2001). Heyera and Berger (2000) found that in the coastal area of the southern Baltic Sea, there was a significant correlation between C& diurnal emission and water temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Soil slurry incubation and geochemical analyses Two soils were used, both sampled near the Italian Rice Research Institute near Vercelli, Italy (for general soil characteristics see Holzapfel-Pschorn and Seiler, 1986). For the main experiment, 'recycled soil' was used, a soil that had been used earlier for growing rice in large microcosms at our greenhouse in Marburg and, thus, had been depleted in organics and nutrients (for details see Conrad and Klose, 1999).…”
Section: Methodsmentioning
confidence: 99%